Incorporating citizen science to study plastics in the environment - Zettler, E. R; Takada, H; Monteleone, B; Mallos, N; Eriksen, M; Amaral-Zettler, L. A (Analytical methods, 2017)
Plastic marine debris is a global problem, but due to its widespread and patchy distribution, gathering sufficient samples for scientific research is challenging with limited ship time and human resources. Taking advantage of public interest in the impact of plastic on the marine environment, successful Citizen Science (CS) programs incorporate members of the public to provide repeated sampling for time series as well as synoptic collections over wide geographic regions. A key challenge with any CS program is to ensure standardized methods and quality control so that the samples and data can legitimately be compared and used in peer-reviewed research. This article describes several successful examples and outlines suggestions for projects cooperating with citizen scientists to provide reliable samples and accurate data, with benefits to science, citizen scientists, and society in general. Plastic marine debris is a global problem, but due to its widespread and patchy distribution, gathering sufficient samples for scientific research is challenging with limited ship time and human resources.